Psychological State of Russian Student Youth in the Crisis: The Relationship with Cultural and Political Patriotism - N.V. Murashcenkova (Moscow State University of Psychology and Education, 2024)
The analysis of markers and determinants of the current psychological state of Russian youth as a risk group with high probability of combined influence on its state of normative crisis of identity and complex external conditions is important and necessary. In the study we conducted a hierarchical regression analysis of the correlation between the severity of psychological trauma associated with the special military operation and with the perception of the future of Russia (dependent variables) and cultural and political patriotism and several control variables (predictors). University students from Moscow, Omsk, Penza, Saratov, Smolensk, Khabarovsk (718 Russian citizens ages 18 to 25, M=19,4; SD=1,46, 21,6% of men) participated in the study. Data were collected in October 2022. We used the Russian version of “International Trauma Questionnaire (ITQ)” and questions from the International Social Survey Programme (ISSP 2013). We found signs of psychological trauma in the third of respondents. The link between the psychological condition of students and cultural and political patriotism and some control variables has been revealed. Cultural patriotism, combined with a low level of political patriotism, has contributed to the psychological trauma of young people in the current crisis. Cultural patriotism combined with political patriotism is a factor of positiv perception of the future of Russia. Based on the results, we presented a portrait of student who is in great need of psychological help.